Contagion nation: a comparison of paid sick day policies in 22 countries - Heymann, Jody; Rho, Hye Jin; Schmitt, John; Earle, Alison (Washington, DC, 2009)
"This report finds that the U.S. is the only country among 22 countries ranked highly in terms of economic and human development that does not guarantee that workers receive paid sick days or paid sick leave. Under current U.S. labor law, employers are not required to provide short-term paid sick days or longer-term paid sick leave. By relying solely on voluntary employer policies to provide paid sick days or leave to employees, tens of millions of U.S. workers are without paid sick days or leave. As a result, each year millions of American workers go to work sick, lowering productivity and potentially spreading illness to their coworkers and customers."